Environmental impacts and resource use for sheep production in semi-arid India investigated by life cycle assessment. (15th April 2022) - Lal, B.; Sarkar, Srobana; Gautam, Priyanka; Meena, R.L.; Bhatt, R.S.; Sahoo, A.
Abstract: Agriculture is a major contributor of green house gas emissions and livestock component have significant contribution, sheep being an important part of animal husbandry also contributes to carbon footprints (CFs) of environment through enteric fermentation, manure emissions and inputs used in sheep husbandry. To augment productivity and lower environmental impact of livestock sector, intensive farming is a promising strategy; yet, the approach of feeding more amount of concentrate to increase the productivity of animals was less competent and severed environmental effects as compared to fodder production. Furthermore, to avoid dependence on grazing pastures and provide year round quality fodder to the animals, carbon foot print from forage production required for stall feeding should be taken in to consideration along with other agromonic practices for conducting life cycle assessment of sheep farming. In this study, rearing of popular sheep breeds (Malpura, Avishaan, Patanwadi and Kheri) along with dominant forage production systems (napier, perennial grasses, forage legumes and bajra) was assessed in terms of carbon foot prints and output of crops as well as sheep. Among the crops, perennial grasses required less input and very low CFs from inputs followed by forage legumes. The mean carbon foot print of finished lambs was 8.9, 9.5, 9.3 and 5.7 kg CO2 e/kg live weight in Malpura, Avishaan, Patanwadi and Kheri, respectively. For production of 1 kg fodder on dry matter basis, Napier required around 224.6% higher carbon input than perennial grasses along with maximum productivity (carbon output) of 67.4% as compared to other crops. Grasses being marginal crops required very low carbon input approximately 794.5% lower as compared to Napier production. For meat, Avishaan proved its superiority in terms of higher meat production which resulted in higher CFs from meat in Avishaan which was around 89.9 and 85.5% higher than Malpura and Patanwadi, respectively. In case of milk, Patanwadi was the highest contributor having 20.1 and 14.3% higher CO2 -e as compared to Malpura and Avishaan, respectively. The CFs for wool production was also more for Patanwadi by about 15.0 and 22.9% higher than Malpura and Avishaan, respectively. When the CFs of fodder production and sheep farming was studied together, it was revealed that Napier production with Patanwadi rearing contributed maximum CFs over other systems. Grass cultivation with Avishaan rearing resulted in least CFs contribution. The results suggest that environmental impact of animal production sector should be conducted considering the mean carbon footprints of all correlated farm variables for indepth information. Graphical abstract: Image 1 Highlights: Carbon footprints of different sheep breeds with on farm forage production were investigated. Sheep rearing with napier resulted in highest CFs from inputs. Avishaan reared with perennial grasses had utmost CFs from output. Enteric CH4 emissions represented the chief contributor (∼30–40%) of CF in each breeds. Sheep farming with perennial fodder grasses has minimum environmental impacts.